Mosque : A statement of citizenship - Sapian, Abdul Razak; Ismail, Mohd Noorizhar; Rashid, Mizanur; Wan Mohd Rani, Wan Nurul Mardiah (Malaysian Institute of Planners, 2018)
Mosque is referred to as a place for Muslim's congregational prayers, a community centre, and a frontage to the Mslim's world Mosque from the start was intended as a sanctuary and home tot he Muslims where they can affiliate in their lives. In Australia, the Afghan cameleers have established the major mosques as they were among the early Muslim settlers of the country after the Makassar Muslims. Afghans Cameleers in Australia are majority muslims in the faraway land of Afghanistan, who migrated to this place of unfamiliarity in order to place themselves in the society while searching for wealth in sustaining and building their reputation in their homeland. This research seeks to explore the idea of citizenship through the concept of belonging and how it translates to architecture and the Islamic built environment. to express the sense of belonging and citizenship in a land where they are unaccepted, the Afghans resort o creating legacy to be accepted and represent their citizenship. This research will study the elements that result tot he citizenship of the Muslim Afghans in Australia. the citizenship approach will focus on the social inference rather than political or constitutional approach as the 1901 immigration law dictates that these people will never be naturalized.